Discovery of a z = 0.65 post-starburst BAL quasar in the DES supernova fields. Issue 3 (23rd March 2017) - Mudd, Dale; Martini, Paul; Tie, Suk Sien; Lidman, Chris; McMahon, Richard; Banerji, Manda; Davis, Tamara; Peterson, Bradley; Sharp, Rob; Seymour, Nicholas; Childress, Michael; Lewis, Geraint; et al.
Abstract: We present the discovery of a z = 0.65 low-ionization broad absorption line (LoBAL) quasar in a post-starburst galaxy in data from the Dark Energy Survey (DES) and spectroscopy from the Australian Dark Energy Survey (OzDES). LoBAL quasars are a minority of all BALs, and rarer still is that this object also exhibits broad Fe ii (an FeLoBAL) and Balmer absorption. This is the first BAL quasar that has signatures of recently truncated star formation, which we estimate ended about 40 Myr ago. The characteristic signatures of an FeLoBAL require high column densities, which could be explained by the emergence of a young quasar from an early, dust-enshrouded phase, or by clouds compressed by a blast wave. The age of the starburst component is comparable to estimates of the lifetime of quasars, so if we assume the quasar activity is related to the truncation of the star formation, this object is better explained by the blast wave scenario.